2018
DOI: 10.1079/pavsnnr201712049
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod pests of date palm and their management.

Abstract: This review lists 132 species of insect and mite pests associated with date palm (Phoenix dactylifera L.) grown worldwide. These species are distributed among eight insect orders and 30 families, besides one order of mite comprising nine families. Most of the species (52) were reported on the leaf (frond), while 26 species were associated with the roots and trunk. Green fruits with their stalks and stored dates hosted 27 species each. Coleoptera represented 41% of the listed pest species, followed by Hemiptera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Organic dates are now produced in many countries around the world including Tunisia, Israel, Saudi Arabia, Egypt, Sudan, Iran, Algeria, and the USA. Date palm, whether grown conventionally or organically, has numerous pests and diseases including 132 species of arthropod (insects and mites), 52 vertebrate pests (birds, rodents, bats), and 28 non-arthropod pests (slugs and snails, parasitic nematode) [26,27]. Additionally, more than 16 important fungal, phytoplasma, and unidentified diseases attack the date palm.…”
Section: A Case Study Of Organic Date Palmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic dates are now produced in many countries around the world including Tunisia, Israel, Saudi Arabia, Egypt, Sudan, Iran, Algeria, and the USA. Date palm, whether grown conventionally or organically, has numerous pests and diseases including 132 species of arthropod (insects and mites), 52 vertebrate pests (birds, rodents, bats), and 28 non-arthropod pests (slugs and snails, parasitic nematode) [26,27]. Additionally, more than 16 important fungal, phytoplasma, and unidentified diseases attack the date palm.…”
Section: A Case Study Of Organic Date Palmsmentioning
confidence: 99%
“…The date palm agroecosystem comprises diverse groups of natural enemies including insect predators, parasitoids, spiders, predatory mites, birds, entomopathogenic nematodes, and microorganisms. In this respect, El-Shafie et al [26] listed 90 species of predators and parasitoids from 9 orders and 23 families. Out of the listed species, the most important are the general predator Chrysoperla carnea and the braconid wasp Bracon spp.…”
Section: Conservation and Enhancement Of Natural Enemies Of Pestsmentioning
confidence: 99%
“…To control these pests, several methods have been investigated, i.e., insecticides, mechanical control, biocide, and natural products (Bekheet and El-Sharabasy, 2015;Gameel, 2017;and Latifian, 2017). The intensive use of traditional chemical insecticides has many serious problems, such as high economic cost, negative impact on the environment and human health, and some pests develop resistance towards them (El-Shafie et al, 2017 andAbdel-Samad et al, 2019). Therefore, chemical pesticides should not be relied upon as short-term solutions against date palm pests to avoid the risk of residues in fruits and to maintain the balance of the ecosystem Aldosari, 2007 andAbdel-Samad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The climate change and the large scale movement of palm species for farming and ornamental gardening, may help in an increasing of the invasive species events compounding the problems of crop protection. El-Shafie et al, (2017) reported 132 species of insect and mite pests associated with date palm grown worldwide. These species are distributed among eight insect orders and 30 families, besides a single order of mites pertaining to nine families.…”
Section: Introductionmentioning
confidence: 99%